The Association between ADHD Symptoms and Antisocial Behavior: Differential Effects of Maternal and Paternal Parenting Behaviors - Selma Salihovic; Xiang Zhao; Terese Glatz (Youth)
The present study examined the moderating role of maternal and paternal behaviors on the association between ADHD symptoms and antisocial behavior. The data are from a Swedish community-based study with 2886 adolescent participants, aged 13–15. We analyzed the adolescents’ self-reports of negative and positive parental behavior, ADHD symptoms, and antisocial behavior. Results show that ADHD symptoms significantly predicted levels of antisocial behavior in both maternal- and paternal-moderated regression models. Also, several significant interaction effects emerged. Fathers’ attempted understanding and mothers’ warmth significantly buffered the association with antisocial behavior. In turn, mothers’ negative behaviors—both coldness and rejection and angry outbursts—significantly enhanced the association with antisocial behavior, whereas only fathers’ angry outbursts emerged as a significant moderator. Thus, there is support for differential effects of maternal and paternal behavior on the association between ADHD symptoms and adolescent antisocial behavior.